Motivation and satisfaction towards two-year vocational diploma - Tanzir Masykar; Febri Nurrahmi (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2020)
Lack of students enrolling in diploma programs compared to what occurred Germany is a sign that Indonesian high school graduates are discouraged from enrolling in the program. Previous studies have mostly focused on the perception and expectation toward vocational high school, leaving motivation and satisfaction under-researched. This study aims to look at the motivation of students enrolling at the two-year diploma and how satisfied they are with the program. Factors contributing to their satisfaction would be presented accordingly. The study used a qualitative research approach with a case study design by examining current students at AKN Aceh Barat. A focus group discussion coupled with interview were employed to obtain the data and a total of 23 first year diploma students participated in the study. The study found that students were encouraged to enroll for the diploma program due to practical skill benefit, short durational advantage, and financial constraints of their families. They valued practical skills over theoretical knowledge and a short time of study over four years in college. The financial constraint also implies that most students enrolled in the program originate from financially unfortunate families. Most students have been satisfied with the program indicating that their initial motivation has been fulfilled. Factors contributing to their satisfaction include practical skills, theoretical knowledge, laboratory facilities, building infrastructure, and the number of students. They have been satisfied with the balance between practical skills and theoretical balance offered by the program yet felt the need for improvement in the other areas.